Theoretical approach of branding from a semiotic perspective - Marcos, Paloma Sanz (IROCAMM - International Review Of Communication And Marketing Mix, 2018)
This paper outlines the importance of the world of signs and symbols relating to brand management. We will explore the traditional semiotics authors and how those have been influenced other academics who have researched branding from a semiotic perception. This research provides a literature revision theoretical of the brand from a semiotic insight considering its theoretical framework and the implementations of some of the analysis models for a deep revision of the implications of semiotics in branding.